Identification of heat shock transcription factor gene families in sunflower and their expression profiles under abiotic stress(向日葵热激转录因子基因家族鉴定及其在非生物胁迫下的表达分析) - 宋慧芳(SONG Huifang); 薛宏宇(XUE Hongyu); 王茜(WANG Xi); 卢俊洁(LU Junjie); 李晨雨(LI Chenyu); 刘阿克(LIU Ake) (浙江大学学报. 农业与生命科学版)
Heat shock transcription factor (HSF) is widely distributed among plants and plays important roles in multiple transcriptional regulatory pathways, particularly in heat stress signaling and other stress responses. In this study, HSF gene family members were identified using bioinformatics methods, and their phylogenetic relationships, gene structures, and expression patterns were analyzed. The results showed that 39 members of HSF family (HaHSF) were identified in sunflower, which were divided into three groups and eight subfamilies, with expansion driven primarily by whole genome duplication and transposed duplication within this gene family. Owing to strong functional constraints, the majority of pairs of duplicate genes have undergone purifying selection. Furthermore, the expression patterns of HaHSF genes were observed in various tissues and under hormone or abiotic stress conditions by analyzing transcriptome analysis. HaHSF12, HaHSF22, HaHSF27, and HaHSF33 showed responsiveness to exogenous plant hormones such as abscisic acid, salicylic acid; while HaHSF17, HaHSF18, and HaHSF33 might be involved in conferring abiotic stress resistance on sunflower seedlings. Coexpression network analysis of genes under heat stress revealed that HaHSF23, HaHSF18, and HaHSF29 were located at the core of the network. The genes coexpressed with them were associated primarily with the response to heat, the response to reactive oxygen species, mitogen-activated protein kinase (MAPK) signaling pathway, and secondary metabolite biosynthesis. A systematic study of HSF gene family in sunflower could provide an important reference for functional studies of HSF family and molecular breeding of sunflower. . 热激转录因子（heat shock transcription factor, HSF）广泛分布于植物中，参与多种转录调控途径，特别是热应激信号传导和其他应激反应。本研究利用生物信息学方法研究HSF基因家族，对其系统发育关系、基因结构和表达模式等进行了分析。结果表明：在向日葵中共鉴定到39个HSF家族成员（HaHSF），并将其分为3个组、8个亚家族；全基因组重复和转座重复是向日葵HSF家族扩增的主要原因。由于功能约束强烈，大多重复基因经历了纯化选择。转录组分析明确了HaHSF基因在不同组织中和激素或非生物胁迫条件下的表达模式。HaHSF12、HaHSF22、HaHSF27和HaHSF33基因能响应脱落酸、水杨酸等外源植物激素；而HaHSF17、HaHSF18和HaHSF33基因可能参与向日葵幼苗的多种非生物抗逆性。高温胁迫下基因的共表达网络分析发现，HaHSF23、HaHSF18和HaHSF29基因处于网络的核心，与其共表达的基因主要参与响应高温、响应活性氧、促分裂原活化的蛋白质激酶信号通路以及次生代谢物生物合成等功能。通过对向日葵HSF基因家族的系统研究，可为后期向日葵HSF基因功能和分子育种研究提供参考。